Multiphase power converter drive for fault-tolerant machine development in aerospace applications - De Lillo, Liliana; Empringham, Lee; Wheeler, Patrick W.; Khwan-on, Sudarat; Gerada, Christopher; Othman, Md Nazri; Huang, Xiaoyan (Institute of Electrical and Electronics Engineers Inc., 2010)
This paper describes an experimental tool to evaluate and support the development of fault-tolerant machines designed for aerospace motor drives. Aerospace applications involve essentially safety-critical systems which should be able to overcome hardware or software faults and therefore need to be fault tolerant. A way of achieving this is to introduce variable degrees of redundancy into the system by duplicating one or all of the operations within the system itself. Looking at motor drives, multiphase machines, such as multiphase brushless dc machines, are considered to be good candidates in the design of fault-tolerant aerospace motor drives. This paper introduces a multiphase two-level inverter using a flexible and reliable field-programmable gate-array/digital-signal-processor controller for data acquisition, motor control, and fault monitoring to study the fault tolerance of such systems.